Sustainable ethylene production in Ecuador: Comparative analysis between naphtha cracking and biomass-based processes using Andean potato waste - Vaca, Gabriel; Quiroga Quisaguano1, Sonia; Rizzo, Kimberly; Pincay, Dimas; Alvarez-Barreto, José (ACI Avances en Ciencias e Ingenierías, 2026)
Ecuador, a country highly dependent on its oil industry, faces the need to import petroleum derivatives due to the lack of a developed petrochemical sector. This study comparatively assesses the technical, economic, and environmental feasibility of three routes for ethylene production, focusing on more sustainable and environmentally friendly processes. The first, the traditional linear process based on thermal cracking of naphtha, is noted for its technological maturity and lower initial costs, but operates under the "extract, produce, dispose" sequence, leading to a high environmental impact due to the substantial energy required and significant greenhouse gas emissions. In contrast, the two proposed circular routes utilize potato agricultural waste as biomass for bio-ethylene production: (a) fermentation to obtain bioethanol followed by catalytic dehydration and (b) electrocatalysis of methane derived from residual biomass. The study's results indicate that while these routes face technical and economic challenges, such as low yields, additional equipment for raw material processing, and higher initial costs, they offer environmental benefits aligned with green chemistry principles, including carbon emission reduction, use of renewable raw materials, and increased energy efficiency. Of the two circular processes analyzed, fermentation is considered the more applicable option due to biomass availability and process maturity in the local industry, despite having a cost 2.6 times higher than the linear process. While naphtha-based ethylene production remains the most viable in economic and technological terms, the development of a sustainable bio-ethylene industry still faces challenges in scalability, yields, and high initial costs but would allow the valorization of agricultural waste, diversifying the country's production matrix and positioning Ecuador as a leader in green innovation in Latin America.
Keywords: bio-ethylene; biomass; catalytic dehydration; electrocatalysis; potato; waste valorization